IMPACTO DE PERTURBAÇÕES NA OPERAÇÃO DE CARGAS CONECTADAS EM SISTEMA DE BAIXA TENSÃO - Kotlinski, Eliseu; Reimbold, Manuel; Appel, Sergio F.; Capinos, Cesar U.; Bauce, Pierre L.; Eder, Ciro J. F.; Turchiello, Gilson M.; Lopes, Henrique C. (Salão do Conhecimento, 2013)
Resumo